Screening for retinopathy of prematurity (ROP) in the middle Black Sea region of Turkey - Beden, Ümit; Demir, Selim; Aygün, Canan; Küçüködük, Sükrü; Erkan, Dilek (The Turkish Journal of Pediatrics, 2012)
This study was designed to determine the frequency of retinopathy of prematurity (ROP) and the effectiveness of the screening protocol in preterm infants for our country. With these objectives, the charts of 1000 preterm infants were reviewed in Ondokuz Mayis University, Department of Ophthalmology. ROP frequency, the effect of gestational age (GA) and birth weight (BW) and the effectiveness of the screening protocol were evaluated. In this study, ROP was observed in 30.8% of infants and not observed in 69.2% of infants. Threshold ROP was detected in 7.0%. The frequency of threshold ROP was 43.5%, 20.0%, 12.6%, and 8.8% in the infants with GA of < or = 26, 26-28, 29-30, and 31-32 weeks, respectively. Threshold ROP was not observed in babies born after 34 weeks. Treatment was required for 11% of the infants. ROP treatment requirement (11%) was limited to babies with GA of < 34 weeks of gestation. Incidence of ROP was inversely proportional with GA and BW. Treatment was not required when GA was > 34 weeks. A new ROP screening protocol is proposed for Turkey, which is: screening of preterm babies with GA of < 34 weeks and BW of < 1800 g.